The potency of Bukit Tapak forest as means for traditional ceremony, environmental conservation, and education - I WAYAN SUMANTERA (Society for Indonesian Biodiversity, 2004)
Bukit Tapak (1903 m) the natural reserve of Batukau I (816.4 ha) is one of three natural reserve area of Batukau (1762.8ha, 1974). Located at the tourism object of Bedugul, the eastern part boundaries to the Botanic Garden Eka Karya-LIPI(154.5 ha, 1959) and settlement of Candikuning area (1152 family, 4475 persons) and near the three lakes of the waterresources of Bali; Beratan, Buyan and Tamblingan lake. The special plants; cemara geseng (Casuarina junghuhniana Miq.),cemara pandak (Dacrycarpus imbricatus (Blume) de Laub.), nyabah (Pinanga arinasaensis J.R. Witono), paku kidang(Dicksonia blumei Planch.), and purnajiwa (Euchresta horsfieldii (Lesch.) Benth.). The pioneer plant of the hill is cemara geseng and the endemic is cemara pandak. The plant of needle leaves that basically the existence of Bali Botanical Garden as the conservation ex situ flora of noodle leaves especially at the eastern Indonesian area. Nyabah, which is supposed to be the new kind of palm named Arinasa, driven from the staff name who is the pioneer of the conservation. Paku kidang is rare. There are ethnobotany plants of ritual ceremony such as: kayu tulak (Schefflera sp.), kayu tulung (Brasaia sp.), penjalin (Calamus sp.), paku pidpid (Nephrolepis sp.), trijata (Medinilla speciosa (Blume ex Mart.) Blume), etc. Balinese people believe that forest is holly and sacred. But because of the existence of Pura Teratai Bang (16 century) at the slope, moslem cemetery (found in 1938) at the peak, and other needs (climbing, food, medicine, etc.), it can not be avoided the entrances of people that caused the forest is damaged. The forest reservation needs the approach to the local people, so the solution are morally and integration. The use of the forest which is potential as the environment education facilities conservation and other alternatives such as: horticulture, the improvement of the people economy discussed here to be the input for the forest conservation wisely and continuously.Â© 2004 Jurusan Biologi FMIPA UNS SurakartaKeywords: Bukit Tapak, traditional ceremony, environment, conservation, education.